Family Food Security and Parenting Patterns with Stunting Event in Toddlers - Ruth Putri Handayani Br Hutahaean; Evawany Y Aritonang; Etti Sudaryati (Universitas Aisyah Pringsewu, 2022)
Stunting is currently experienced by many toddlers in the world, especially in developing countries including Indonesia. Stunting is not only associated with children's height that is shorter than their age but can also threaten the intelligence, disease resistance, quality, and productivity of future generations. This study aims to analyze the relationship between family food security and maternal parenting with the incidence of stunting in toddlers aged 24-59 months. The study was observational and cross-sectional design. The sampling technique was multistage random sampling with a sample size of 205 children. Data were analyzed analysis using chi-square and multiple logistic regression tests. The results showed that there was no significant relationship between family food security (p=0.100) and the incidence of stunting, there was a significant relationship between breastfeeding and food parenting (p less than 0.001), hygiene parenting, and environmental sanitation (p less than 0.001) with stunting in toddlers aged 24-59 months. The multivariate results showed that the variables most related to the incidence of stunting were hygiene parenting and environmental sanitation where the p-value was 0.003 and the PR value was 10,844 (95% CI=2.234-52.639). It is expected that health workers will monitor the nutritional status of children under five, and need to increase mother's knowledge about good parenting and the importance of improving clean and healthy living behavior.Abstrak: Stunting saat ini banyak dialami oleh balita di dunia, terutama di negara berkembang termasuk Indonesia. Stunting tidak hanya dikaitkan dengan tinggi badan anak yang lebih pendek dari usianya, tetapi juga dapat mengancam kecerdasan, ketahanan terhadap penyakit, kualitas, dan produktivitas generasi mendatang. Penelitian ini bertujuan untuk menganalisis hubungan ketahanan pangan keluarga dan pola asuh ibu dengan kejadian stunting pada balita usia 24-59 bulan. Jenis penelitian adalah observasional dan desain cross-sectional. Teknik pengambilan sampel adalah multistage random sampling dengan jumlah sampel 205 anak. Analisis data menggunakan uji chi-kuadrat dan regresi logistik berganda. Hasil penelitian menunjukkan bahwa tidak ada hubungan yang signifikan antara ketahanan pangan keluarga (p=0,100) dengan kejadian stunting, ada hubungan yang signifikan antara pemberian ASI dengan pola asuh makanan (p kurang dari 0,001), higiene pola asuh dan sanitasi lingkungan (p kurang dari 0,001). dengan stunting pada balita usia 24-59 bulan. Hasil multivariat menunjukkan bahwa variabel yang paling berhubungan dengan kejadian stunting adalah higiene parenting dan sanitasi lingkungan dimana p-value 0,003 dan nilai PR 10.844 (95% CI=2.234-52.639). Diharapkan petugas kesehatan memantau status gizi balita, dan perlu meningkatkan pengetahuan ibu tentang pola asuh yang baik dan pentingnya meningkatkan perilaku hidup bersih dan sehat.